Neokaisaria (Pieria): A case study of recent mass migration from western Macedonia to federal Germany - Kolodny, Emile (The Greek Review of Social Research, 1981)
Amongst contemporary Greek migrations, migratory waves towards West Germany can be distinguished by their recent and massive character, their special function as a supply of· unskilled industrial manpower, as well as their precise geographical origins. Most of those migrants came from Macedonia, a region united to Greece after the first Balkan War (1912). The population of this area was fundamen tally altered by the Greek-Turkish compulsory exchanges of 1922-23 and the arrival of numerous refugees from Asia Minor. Neokaisaria, a small settlement near Katerini (Pieria), was founded in 1928 by refugees from the Pontus mountains. Since 1961, the village has lost half of its inhabitants through mass migration to West Germany. Between 1975 and 1977, a parallel survey has been carried out in Neokaisaria and in the Stuttgart conurbanization area, where these migrants are mainly concentrated. This study is based on the analysis of basic documents, Greek and German unpublished sources, and matched from interviews on individuals. The Neokaisaria case study offers a concrete example of today migratory movements in rural Macedonia. This monography is an outcome of a more general geographical project conducted by the French National Center for Scientific Research K NRS RCP n° 397), dealing with labour migra tions between Mediterranean countries and West Germany.